DIGITAL RIGHT MANAGEMENT: SAFEGUARDING COPYRIGHT IN THE CYBER ERA - Atanasova, Irina (Annals of Spiru Haret University. Economic Series, 2024)
Copyright infringement is commonly perceived as a private economic transgression, typically addressed through private legal actions and remedies. The advent of digitalization, encompassing copyrighted works such as text, music, and video, has enhanced unauthorized reproduction. The ubiquity of the Internet enables infringers to replicate thousands of copyrighted works at minimal cost. This article outlines the methodologies of digital rights management (DRM), clarifying its protective mechanisms and highlighting the adverse consequences associated with DRM implementation. As a technological framework, DRM is specifically engineered to prevent unauthorized copying of digital content. It assumes a pivotal role in safeguarding content exchanges within the digital landscape, thereby minimizing copyright infringement and plagiarism. The paper further explains potential future trends in copyright protection and the evolving landscape of DRM.